Pengaruh penerapan LKS virtual laboratory dalam pembelajaran konstruktivisme terhadap pencapaian kompetensi fisika siswa kelas XI SMAN 15 Padang - Yuri Yanti; Masril Masril; Hidayati Hidayati; Yenni Darvina (Universitas Negeri Padang, 2019)
Achieving the physics competence students in high school has not optimal. This case is caused by low students learning activities in the learning process, teachers rarely assosiate the material learned with the previous material so that students are less motivation to learned. For it used constructivism learning approach which are helped by virtual laboratory worksheet. The purpose of this reseach is to improve the physics competence achievement through the constructivism learning approach and virtual laboratory worksheet at grade XI of SMAN 15 Padang. This reseach used is a Quasi Experiment reseach with Factorial Design 2x2. The population this reseach was the students of grade XI MIA in SMAN 15 Padang which registered at he academic year of 2018/2019. The samples taken by using Purpose Sampling. The instruments are observation sheet for attitude competence, post-test for the knowledge competence, performance for skills competence. The data of attitude competence obtained were analyzed by using chart analysis and the data of the knowledge and skill competence were analysis by using two directions of variant. Based on the research conducted and data analysis. Fisrt, average attitude competence of the experiment class more than the control class. Second, knowledge and skill competence shows that the first working hypothesis is accepted while the second and third hypothesis is rejected. This shows that there are significant effect of applying the virtual laboratory worsheet in constructivism learning towards the students attitude, knowledge and skill of cmpetence at the 0,05 α.